213k views
3 votes
|||

Finding the average rate of change of a function given its...
Find the average rate of change of g (x) = -2x²-x from x = 1 to x = 6.
Simplify your answer as much as possible.
0
18 08
X
k

User Sahil
by
6.2k points

1 Answer

3 votes

Answer:

Mind you that the average rate of change is the gradient. Commonly we get it by using the formula that requires us to have also the y coordinates.

we can find them by plugging in the x-values in the function g(x)

x=1


g(1)=-2(1^(2) )-1\\g(1)=-3\\\\g(6)=-2(6^(2))-1\\ g(6)=-73

now we have the points (1,-3) and (6,-73)


m=(y2-y1)/(x2-x1)

that is the formula we will use


=(-73-(-3))/(6-1) \\=(-70)/(5) \\=-14

User Nikksan
by
6.0k points